Toward a Model of Work-Related Self: A Narrative Review - Knez, Igor (Frontiers in Psychology, 2016)
Occupational work as personal and social identification can be conceptualized as one of the life goals that we strive for and find meaning in. A basic categorization of the phenomenon of work-related identity is suggested, based on psychological theories of identity, memory and relational schema. It distinguishes between organizational, workgroup and professional identity. The two former relate to the concepts of social identity and collective self and the latter to the concepts of personal identity and individual self. These are assumed to form functionally independent cognitive structures, leading to separate motivations and influences on work-related satisfaction. Given this, empirical research on the impact of work-related identity on employee satisfaction, in general terms, is reviewed. The article concludes with some prospective directions for future research by sketching a general model of work-related self. It is hypothesised to evolve by a causal progression from employment across time via emotional and cognitive components.